The Acute and Frequency Dose Effects of High Intensity Functional Training on Cardiometabolic Health, Fitness, and Exercise Enjoyment in Adults With Metabolic Syndrome - Smith, Erin (Auckland University of Technology, 2024)
Metabolic syndrome (MetS) increases the potential of developing atherosclerotic cardiovascular disease (ASCVD), type 2 diabetes (T2D), and several common cancers. The reported prevalence of MetS is as high as 31% in the global adult population, rendering it a predominant driver of the worldwide crisis of the aforementioned diseases. There is mounting evidence demonstrating that regular exercise has a profound effect in improving MetS, however, only one in four adults worldwide meet the minimum exercise recommendations. The most commonly reported barriers to this are “lack of time,” “lack of facilities,” and “lack of motivation”. Rising in popularity is a time-efficient form of exercise known as high-intensity functional training (HIFT), which provides workout design options that require minimal equipment and adaptability to various physical settings. HIFT has also shown to elicit positive psychological affect, leading to exercise adherence. HIFT shows promise as a strategy for mitigating the barriers to regular exercise participation. However, the effects of HIFT on cardiometabolic health are not fully understood. Thus, the primary focus of this PhD was to conduct a series of cohesive investigations in order to answer the overarching research question, What are the frequency dose effects of HIFT on cardiometabolic health in adults with MetS? This thesis is constructed in two sequential parts to reflect the flow of investigation of this novel modality of exercise. The aim of Part 1 was to determine the acute responses to a unique HIFT design in an untrained population with MetS. Part 1 established the process for the 3-week familiarization period that was implemented in Part 2. Part 1 ascertained that the exercise intensity of our 50-min HIFT design was considered vigorous, (72.8 ± 10.7% to 81.5 ± 8.8% of maximal oxygen consumption (VO2max)) and exercise-attributed energy expenditure was 270 ± 77.3 kcal. Furthermore, Part 1 explored the acute blood lipid, glucose and vascular endothelial responses, to inform potential chronic adaptations in Part 2. These outcomes demonstrated that a single session of our unique HIFT design had the potency to elicit lasting benefits in blood triglyceride (TG), very low-density lipoprotein cholesterol (VLDL-C), triglyceride/high-density lipoprotein cholesterol ratio (TG/HDL-C), and vascular endothelial function for 24 hours after exercise. The aim of Part 2 was to explore the training effects of three different weekly frequencies (HIFT1 = one day/week; HIFT2 = two days/week; HIFT3 = three days/week) of our HIFT design in a 12-week, periodized intervention. Focusing on the overarching research question, no statistical difference was found between the three frequency dose groups in all primary outcome variables. However, effect size calculations demonstrated that HIFT2 elicited clinically meaningful improvements in blood glucose, waist circumference, vascular endothelial function, and the metabolic syndrome severity score (MSSS); greater than the improvements seen in HIFT1 and HIFT3. A secondary aim of Part 2 was to explore if the perceptions of “exercise enjoyment” and “intention to continue” were different between the frequency dose groups. No differences were found, as all three groups reported similarly high levels of enjoyment and intention to continue. The clinical implications of these results suggest that HIFT, a time-efficient, translatable, and enjoyable modality of exercise, shows promise as a strategy to lessening the worldwide MetS burden. If performed twice weekly, meaningful improvements in MetS can be seen within 12-weeks. This thesis, as a whole, contributes new knowledge to the emerging body of HIFT literature, with wider implications of informing future exercise recommendations for the public.